As ações do instituto do patrimônio histórico e artístico Nacional – IPHAN para a proteção do patrimônio cultural na Sociedade de risco: uma crítica à luz do tombamento federal do centro histórico de São Luís - MA - FERNANDES, Natália de Andrade (2019)
This research discusses the implementation of the tombamento to the cultural heritage protection in the risk society. The tombamento of the architectural structures, secured by the Institute of National Artistic and Historical Heritage – IPHAN, at the Historical Downtown Area of São Luís – MA was analyzed, since the United Nations Educational, Scientific and Cultural Organization – UNESCO awarded it the World’s Heritage title in 1997. Firstly, the research identified the dichotomy between the traditional versus the modern paths, through the Anthony Gidden’s reflexivity and the risk society theory of Ulrich Beck, on the development of São Luís City, specifically on the historical downtown area. The reflexivity addressed by Giddens is one of the foundations of the risk society developed by Beck. Both of them analyze the social structure and consequently the Sociology from the modernity and postmodernity angles. All this debate was driven by the dichotomy between the traditional versus the modern paths and it was canalized for the analyses of the São Luís’ historical downtown area as the research was advancing. Secondly, the researcher discussed legal concept of cultural heritage and its implications in Administrative and Environmental Law as collective good. The research also sought the historical evolution of the cultural heritage and the tombamento’s appliance on the cultural protection of the collective good, also verifying the acceptance of Decree-Law no. 25/37 by the 1988’s Brazilian Constitution. Subsequently, the research will define the local of study, namely the historical downtown area of São Luís City, managed by IPHAN, as well as verify its actions regarding the protection of this area since the UNESCO’s title of Humanity Heritage using the analysis of the federal autarchy. Finally, the historical downtown area protection will be related to the Ulrich Beck’s risk society. The methodology of this research is classed as interdisciplinary, basic, transversal, exploratory, descriptive, qualitative, biographical and documental, with emphasis on the use of field research and interviews with the last two IPHAN supervisors to perceive under the perspective of the managers the autarchy’s actions for the protection of the historical downtown area of São Luís City. Developing this research and following its methods, one expects the actual compression of the cultural heritage protection through the tombamento’s instrument at the historical downtown area of São Luís City connecting with the risk society theory.